KONSEP PENDIDIKAN AKHLAK UNTUK SISWA PONDOK PESANTREN (TINJAUAN KITAB AKHLAK LIL BANIIN KARYA UMAR BIN AHMAD BARAJA’) - Masrifah, Rofiah (IAI Al-Mawaddah Warrahmah Kolaka, 2021)
This research is expected to be able to answer the anxiety about the dangers of juvenile delinquency which causes damage to the morals of the younger generation, this danger not only threatens the environment of children in general but can also affect the Islamic boarding school environment, this can occur through negative influences from cellphones or from bad influences. which is under by students into the boarding school environment. Therefore, it takes a concept of good moral education to create a school environment with good morals so that young generations can be born who are not only intellectual but also have noble character